The graphical method of pauses detection in English speech signals - MARTYNOVA, E. V; EREMEEVA, G. R; VALIEVA, G. F (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThis paper is devoted to the problem of pauses detection in English speech signals. The aim of the current study is to create a new method of speech pauses detection that has no drawbacks other algorithms suffer from. The analysis of it suggests the opportunity to use the graphical method in real-time applications. The article provides a new vision and a new solution of pauses detection problem. The result of the study – the graphical method – may be applied to real-time signal processing, text-to-speech synthesis or used to enrich knowledge about the specified problems.RESUMENEste artículo está dedicado al problema de la detección de pausas en las señales de habla en inglés. El objetivo del estudio es crear un nuevo método de detección de pausas del habla que no tenga inconvenientes de otros algoritmos. Su análisis sugiere la oportunidad de utilizar el método gráfico en aplicaciones en tiempo real. El artículo proporciona una nueva visión y una nueva solución del problema de detección de pausas. El resultado del estudio, el método gráfico, puede aplicarse al procesamiento de señales en tiempo real, la síntesis de texto a voz o utilizarse para enriquecer el conocimiento sobre los problemas especificados.